Corporate social responsibility’s effect on the cost of equity capital during the financial crisis - Muinonen, Suvi (My University, 2016)
This study examines corporate social responsibility’s (CSR) effect on the implied ex ante cost of equity capital with a S&P500 data during sample period 2002-2013. In ad-dition, the relation between CSR and firm riskiness is analysed during the financial crisis period 2007-2009. The findings indicate that CSR investments have not decreased companies’ financing costs, but the impact has been rather neutral. Also, companies that have invested in CSR have not benefit from it during financial crisis compared to com-panies with low CSR. Furthermore, the impact of controversial business areas on the cost of equity capital is scrutinized. This study shows that companies involved in con-troversial benefit from slightly lower financing costs. This result holds even during the financial crisis period. The findings of this study indicate that the markets do not price the CSR activities. Thus, companies with higher CSR involvement do not benefit from lower financing costs from the capital markets. The CSR literature has not been able to fully explain CSR’s effect on firm valuation, and therefore there is no solid evidence about how CSR actually impacts on valuation. However, this study claims that CSR does not have an impact on the cost of equity capital, and therefore companies do not profit from lower financing costs by investing in CSR practices.
Keywords: Corporate social responsibility; Cost of equity premium; stakeholder theory; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|